(untitled) (Global Journal of Human-Social Science, 2023)
Purpose The research was conducted to test the effects of coding activities on the development of children with autism Method Five children aged 6-8 who received education from a special education application center in Erzincan city center participated in the research In the study coding activities consisting of four sessions two sessions a week were made for two weeks Coding activities consist of shadow finding mate finding pattern creation and completion activities Dunn Sensory Profile for mothers in order to determine the effect of coding activities Interview Form and Questionnaire for teachers Concept Evaluation Form was applied to children Results As a result of the research it was determined that coding activities increased the multi-sensory processing attention visual perception interest and acting in accordance with instructions motor hand-eye coordination imitation ability interest fun memory retention eye contact and conceptual skills of children with autism In addition it was determined that children with autism increased their ability to match and complete objects find the shadow of objects and create patterns in relation to the application Discussion and Recommodation In line with the results it is recommended that coding activities be integrated into the educational environments of children with autism